Evaluation of a less invasive cochlear implant surgery in OPA1 mutations provoking deafblindness - Tekin, Ahmet Mahmut; Baelen, Hermine; Heuninck, Emilie; Bayazıt, Yıldırım Ahmet; Mertens, Griet; Rompaey, Vincent van; Heyning, Paul van de; Topsakal, Vedat (NLM (Medline), 2023)
Cochlear implantation (CI) for deafblindness may have more impact than for non-syndromic hearing loss. Deafblind patients have a double handicap in a society that is more and more empowered by fast communication. CI is a remedy for deafness, but requires revision surgery every 20 to 25 years, and thus placement should be minimally invasive. Furthermore, failed reimplantation surgery will have more impact on a deafblind person. In this context, we assessed the safety of minimally invasive robotically assisted cochlear implant surgery (RACIS) for the first time in a deafblind patient. Standard pure tone audiometry and speech audiometry were performed in a patient with deafblindness as part of this robotic-assisted CI study before and after surgery. This patient, with an optic atrophy 1 (OPA1) (OMIM#165500) mutation consented to RACIS for the second (contralateral) CI. The applicability and safety of RACIS were evaluated as well as her subjective opinion on her disability. RACIS was uneventful with successful surgical and auditory outcomes in this case of deafblindness due to the OPA1 mutation. RACIS appears to be a safe and beneficial intervention to increase communication skills in the cases of deafblindness due to an OPA1 mutation. The use of RACIS use should be widespread in deafblindness as it minimizes surgical trauma and possible failures.
Keywords: Sensorineural Hearing Loss; Otogenetics; Genetic Deafness; Hereditary Hearing Impairment; Deafblindness; Genetic Analyses on Sensorineural Hearing Loss; Image Guided Surgery; Robot Assisted Cochlear Implantation Surgery